2011
DOI: 10.1016/j.jpainsymman.2010.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Buprenorphine for the Treatment of Chronic Noncancer Pain in the Oldest Old

Abstract: Our experience confirms the analgesic activity and safety of buprenorphine TDS in the elderly. There was an improvement in mood and a partial resumption of activities, with no influence on cognitive and behavioral ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 23 publications
0
36
1
1
Order By: Relevance
“…31,33,50,52 All 12 of these studies also found transdermal buprenorphine to be well tolerated in the treatment of general chronic pain. 31,33,36,[40][41][42][48][49][50][51][52]55 All of the 15 studies examining chronic low back pain (10 studies) or osteoarthritis pain (5 studies) demonstrated effective pain relief for transdermal buprenorphine, including 1 osteoarthritis study that examined solely elderly populations. 14,34,35,37,38,43,44,46,47,53,54,[56][57][58][59] These studies also examined parameters associated with quality of life, and all 15 demonstrated improvements in activities of daily living (lifting, bending, working), sleep, and/or physical and mental health in response to treatment with transdermal buprenorphine.…”
Section: Transdermal Formulationmentioning
confidence: 97%
See 3 more Smart Citations
“…31,33,50,52 All 12 of these studies also found transdermal buprenorphine to be well tolerated in the treatment of general chronic pain. 31,33,36,[40][41][42][48][49][50][51][52]55 All of the 15 studies examining chronic low back pain (10 studies) or osteoarthritis pain (5 studies) demonstrated effective pain relief for transdermal buprenorphine, including 1 osteoarthritis study that examined solely elderly populations. 14,34,35,37,38,43,44,46,47,53,54,[56][57][58][59] These studies also examined parameters associated with quality of life, and all 15 demonstrated improvements in activities of daily living (lifting, bending, working), sleep, and/or physical and mental health in response to treatment with transdermal buprenorphine.…”
Section: Transdermal Formulationmentioning
confidence: 97%
“…All 12 studies of general chronic pain demonstrated the efficacy of transdermal buprenorphine in pain relief, including 2 (17%) studies assessing an elderly population. 31,33,36,[40][41][42][48][49][50][51][52]55 Of these, 4 (33%) studies also observed various quality of life parameters, with all 4 showing improvements in general quality of life, sleep duration, and/or need for breakthrough analgesia. 31,33,50,52 All 12 of these studies also found transdermal buprenorphine to be well tolerated in the treatment of general chronic pain.…”
Section: Transdermal Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Opioids may be appropriate for use in the elderly under close supervision, sometimes at reduced doses [24], or as low-dose transdermal treatment, e.g., buprenorphine [73, 74]. Recently, tapentadol extended-release has shown promise in the treatment of moderate to severe chronic pain related to OA [75, 76].…”
Section: Current Analgesics Used To Treat Arthritis-related Painmentioning
confidence: 99%